KEPEMIMPINAN PARTISIPATIF KEPALA SEKOLAH: MENDORONG KETERLIBATAN GURU DAN SISWA DALAM PENGAMBILAN KEPUTUSAN - Andrianto, erwin (Social Science Academic, 2024)
Leadership in the educational environment plays a very important role in creating a conducive learning atmosphere. As with participatory leadership, the role of the school principal is not only as a decision-maker but also as a facilitator who encourages the participation of teachers and students. This approach is expected to promote the involvement of all parties in the decision-making process related to education. Teacher involvement is a key element in creating an effective learning environment. In addition to teachers, student involvement is also very important in making decisions related to school policies.The method used in this article is a literature study, which is a data collection approach by reviewing and understanding theories from various literature sources relevant to the research topic. Data collection is done by searching for and constructing information from various sources, such as books, journals, and previous research.The role of the principal in making and taking decisions, with responsibility for results that align with the issues at hand, and the involvement of teachers in decision-making, has a significant impact on improving teacher quality, such as mastery of subject matter and teaching techniques, as well as from the aspects of morale, work ethics, and motivation in carrying out their duties and responsibilities. Additionally, involving students in decision-making allows them to think critically and analytically. This participatory leadership is very important for the principal in the decision-making process because it involves teachers and students, thereby forming a shared goal that creates a conducive and comfortable learning environment.